Peningkatan Pemahaman Abhidahamma Pitaka Melalui Mind Mapping Pada Mahasiswa STABN Raden Wijaya - Tri Suyatno (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
The Abhidhamma Pitaka is a part of the Tripitaka scriptures. Abhidhamma learning can be said to be a difficult subject because it contains the teachings of metaphysics in Buddhism where there is a lot of Pali language and various terms in it, many charts. Using the mind map method can make it easier to understand the Abhidhamma Pitaka material.